Characterization of nonlinear behavior of an airfoil under stall-induced pitching oscillations - Vasconcellos, R. M.G. [UNESP]; Pereira, D. A.; Marques, F. D. (Elsevier, 2016)
This work presents an investigation on the embedded dynamics of experimental aeroelastic signals of an airfoil under the influence of stall-induced oscillations. Helicopter blades or wind turbines are severely imposed to vibrate in stall conditions, which motivates this research. Despite a significant effort to model the unsteady aerodynamics associated with the stall phenomenon, nonlinear aeroelastic behavior prediction and analysis in such flow regime remain formidable challenges. This modeling requires proper knowledge of the physical events during stall regime, what can be better attained from experimental data. In this work a pitching airfoil is tested in a wind tunnel model. Due to the stall influence the airfoil presents sustained periodic and limit cycle oscillations at high angles of attack. The influence of wind-off preset incidence angles are also included in these analyses. The aeroelastic signals are evaluated using techniques from time series theory and spectral analysis. The method of delays approach is used to reconstruct the state space, revealing indications to possible bifurcations and complex dynamics. Changes in amplitudes of stall-induced oscillation due to airspeed and preset angles increases were also investigated. Frequency domain analysis through power spectra evolutions and higher-order spectra was used to identify and confirm nonlinear couplings and other complex features.